A highly luminescent octanuclear gold(i) carbide cluster. Issue 64 (27th July 2017) - Feuerstein, Thomas J.; Poß, Marieke; Seifert, Tim P.; Bestgen, Sebastian; Feldmann, Claus; Roesky, Peter W.
Abstract : An octanuclear gold(i ) carbide bridged amidinate cluster [Au8 {μ3 -(η 1 :η 2 -CC)}2 (Me3 SiCCC(NDipp)2 )4 (tht)2 ], which is the first gold(i ) complex with a μ3 -η 1 :η 2 carbide coordination, has been synthesized. The cluster shows intense luminescence with notable high quantum yields both in the solid state and in solution. Abstract : The ligand [{Me3 SiCCC(NDipp)2 }Li(thf)3 ] (Dipp = 2, 6-diisopropylphenyl) was used for salt metathesis reactions with [AuCl(tht)] (tht = tetrahydrothiophene) to obtain the dinuclear alkyne functionalized bisamidinate [{Me3 SiCCC(NDipp)2 }2 Au2 ]. This compound serves as a building block for the polynuclear carbide bridged gold(i ) amidinate complex [Au8 {μ3 -(η 1 :η 2 -CC)}2 (Me3 SiCCC(NDipp)2 )4 (tht)2 ], which is the first gold(i ) complex with a μ3 -η 1 :η 2 carbide coordination. Both gold(i ) compounds show distinct aurophilic interactions and are remarkably stable at ambient conditions. Photophysical investigations revealed intense luminescence with notable high quantum yields both in the solid state and in solution.